The Autism and Angelman Syndrome Protein Ube3A/E6AP: The Gene, E3 Ligase Ubiquitination Targets and Neurobiological Functions - Khatri, Natasha; Man, Heng-Ye (Frontiers in Molecular Neuroscience, 2019)
UBE3A is a gene implicated in the neurodevelopmental disorders. The protein product of UBE3A is the E3 ligase E6AP, and its expression in the brain is uniquely regulated via genetic imprinting. Loss of E6AP expression leads to the development of Angelman syndrome, clinically characterized by lack of speech, abnormal motor development, and the presence of seizures. Conversely, copy number variations (CNVs) that result in the overexpression of E6AP are strongly associated with the development of ASDs, defined by decreased communication, impaired social interest, and increased repetitive behavior. In this review, we focus on the neurobiological function of Ube3A/E6AP. As an E3 ligase, many functional target proteins of E6AP have been discovered, including p53, Arc, Ephexin5, and SK2. On a neuronal level, E6AP is widely expressed within the cell, including dendritic arbors, spines, and the nucleus. E6AP regulates neuronal morphological maturation, and plays an important role in synaptic plasticity and cortical development. These molecular findings provide insight into our understanding of the molecular events underlying AS and ASDs.